The Effectiveness of the Baamboozle Game Strategy on Vocabulary Mastery among Seventh-Grade Students of MTs Al-Mujahidin 1 Samarinda - Siti Sarah; Rostantin Toba; Anis Komariah (Journal of Cultural Narratives in Digital Society, 2026)
This research aimed to examine whether the Baamboozle game strategy is effective on the vocabulary mastery among seventh-grade students of MTs. Al-Mujahidin 1 Samarinda in academic year 2025/2026. This research employed a quantitative experimental design. The population consisted of seventh-grade students of MTs. Al-Mujahidin 1 Samarinda. The sample was divided into two classes, namely class VII-B as the experimental class and class VII-A as the control class. Each class consisted of 16 students. The instrument used in this research was a test in the form of multiple-choice questions administered through pre-test and post-test. The data were analyzed using the normality test, homogeneity test, and hypothesis test (independent sample t-test) to determine whether there was a significant difference between both classes. The finding showed that the mean score of the experimental class in the pre-test was 44.75 and increased to 72.50 in the post-test. Meanwhile, the control class obtained a pre-test mean score of 55.00 and the post-test mean score of 63.25. The result of the independent sample t-test showed a significance value of 0.037, which is lower than 0.05. Therefore, the H0 was rejected and Ha was accepted. It indicated that the use of the Baamboozle game strategy had a statistically significant effect on the vocabulary mastery among seventh-grade students of MTs. Al-Mujahidin 1 Samarinda in academic year 2025/2026.